Dasar Public Speaking - Dika Setiawan; Fahmi Susanti; Feybe Sriningsi Sinaga; Akbar Anugrah Pratama (Advances In Education Journal, 2025)
Developing good communication abilities as a basic requirement for entering the workplace is expected of Vocational High School (SMK) pupils. Still, many SMK students have difficulties forming ideas, lack confidence, and get nervous when speaking in front of others. Often arising from poor command of fundamental public speaking skills and insufficient practice opportunities, these barriers Responding to these obstacles, the Community Service Program (PKM) has been introduced to give 30 SMK Tadika Pertiwi students elementary public speaking instruction. Interactive and hands-on techniques including lesson presentation, group discussions, presentation simulations, and self-practice sessions were used in the training. Positive outcomes were achieved: pre-test and post-test ratings indicated a noticeable improvement in pupils' grasp of public speaking ideas, organizational skills, vocal quality, body language utilization, confidence level, and diminished anxiety. Most participants said they felt more ready to speak in front of their classmates after completing the program and more confident. Ultimately, PKM instruction has successfully sharpened students' fundamental public speaking abilities and ready them for the communication expectations of the professional world.